TOURIST SATISFACTION AS MEDIATING PERCEIVED QUALITY, PUSH MOTIVATION AND PULL MOTIVATION EFFECT TOWARD DESTINATION LOYALTY - Kurniawati, Yenny; Prihandono, Dorojatun (Universitas Negeri Semarang, 2019)
Tourism is a service industry sector that is growing so that managers must develop tourist destinations to increase tourists. This study aims to examine the effect of perceived quality, push motivation, and pull motivation on Pancer Door Pacitan Beach tourists towards destination loyalty with tourist satisfaction as veriable intervening. The population in this study is the Pancer Door Beach tourists whose numbers are unknown. The sampling technique uses purposive sampling, the sample used is taken using the iteration formula. The data collection method uses the questionnaire and documentation method. The method of data analysis using partial test and path analysis.. The results showed that perceived quality, push motivation and tourist loyalty had a positive effect on destination loyalty. While pull motivation does not positively affect destination loyalty. Path analysis results states that tourist satisfaction can mediate perceived quality, push motivation and pull motivation towards destination loyalty. Advice that can be given to the manager of the pancer door beach is the need for improvement in the quality of tourist destinations related to tourist facilities, so that tourists visiting the Pancer Door Beach feel comfortable in making a tour and are satisfied with the attraction offered at Pancer Door Beach. For further researchers to examine different subjects and add other variables that can affect destination loyalty.